Antibody Fc : linking adaptive and innate immunity - Ackerman, Margaret E.; Nimmerjahn, Falk (Elsevier/Academic Press, 2014)
Antibody Fc is the first single text to synthesize the literature on the mechanisms underlying the dramatic variability of antibodies to influence the immune response. The book demonstrates the importance of the Fc domain, including protective mechanisms, effector cell types, genetic data, and variability in Fc domain function. This volume is a critical single-source reference for researchers in vaccine discovery, immunologists, microbiologists, oncologists and protein engineers as well as graduate students in immunology and vaccinology.